(untitled) (Research, Society and Development, 2024)
Apnea of prematurity is a common diagnosis in neonatal intensive care units, especially in preterm patients under 35 weeks or patients born with low birth weight (<1500g). From this perspective, the use of caffeine citrate has short and long-term benefits in this pathology, in addition to reducing the incidence of complications. Methodology: A narrative review of the literature was carried out using the PUBMED database, using the following keywords: “Apnea Prematurity”, “Caffeine” and “Treatment”, with a 6-year filter, analyzing 164 articles, of which only 34 were included and 130 were excluded. Results and Discussion: Apnea of prematurity is a common pathology in preterm and extremely preterm infants, with an incidence of 10% of newborns after 34 weeks and 20-85% of newborns born between 30-34 weeks. The pathophysiology of the disease is explained by the immaturity of the central nervous system in maintaining respiratory drive, in addition to impaired sensitivity in response to chemoreceptors and difficulty in maintaining REM sleep, in addition to the chronic losses inherent to chronic hypoxia. Methylxanthines, the active ingredient in caffeine, have the activation mechanism of inhibiting adenosine A1 and A2 receptors coupled to G protein. The recommended initial dose for therapy is 10 mg/kg for apnea of prematurity, but it must be monitored with concentrations serum levels of the drug to a safe therapeutic range, in addition to monitoring side effects in view of the patient’s clinical impairment. The main signs of side effects from the use of caffeine are tachycardia, hyperglycemia, reduced growth rate, jaundice, irritability, agitation and convulsions. Conclusion: Apnea of prematurity is a very prevalent pathology in preterm newborns and its therapeutic possibility must be taken into account in view of its possible short and long-term complications, since the use of methylxanthines has different evidence of clinical improvement.